Confessions and Tweets: Social Media and Everyday Experience in the Israel Defense Forces. Issue 2 (April 2021) - Stern, Nehemia; Shalom, Uzi Ben
This article explores the social media postings of Israel Defense Forces (IDF) soldiers on two different and unofficial Facebook groups. While scholars of armed forces and society have noted the growing importance that militaries have placed on digital media, there is little data regarding the unofficial uses and meanings that regular soldiers themselves make of social networking sites. With an anthropological focus on everyday experiences, we argue that the social media activity of IDF personnel highlights the quotidian aspects of military life in ways that reverberate beyond the strictly ideological or political facets of their service. Here, soldiers can express their frustrations with military bureaucracy, while also presenting a lighthearted (and positive) commentary on a shared rite of passage. This research opens a window into the lives and dilemmas of the first generation of Israeli soldiers to employ new media as a taken for granted aspect of their service.